Virtual learning platforms: Analysis from its adaptation to learning styles [Plataformas virtuales de aprendizaje: Análisis desde su adaptación a estilos de aprendizaje] (2019)
The promotion of virtual education is a strategic decision within the development plans of the government of Antioquia, which aim to offer its population more access to higher education with quality, taking advantage of the current advantages offered by virtual teaching platforms. The department of Antioquia, Colciencias, KUEPA and the University of Medellín have joined to this purpose, contributing through financing, research and application of knowledge to the project that seeks to improve the teaching-learning processes by means of the inclusion of learning styles in the virtual platform developed by the Colombian company KUEPA. Firstly, this article includes the theoretical description of the teaching process and the factors that influence it. Secondly, the description and comparison of the models that define the learning styles used in similar virtual platforms, and finally, a methodology is described to identify the main sections that provide valuable information about user interactions and their preferences in the learning process. Based on the indicators, the user profile can be defined. © Universidad del Zulia. All rights reserved.